Proceedings of the Proceedings of the 1st International Conference on Religion and Mental Health, ICRMH 2019, 18 - 19 September 2020
DOI: 10.4108/eai.18-9-2019.2293455
|View full text |Cite
|
Sign up to set email alerts
|

Religious Practices as Stress Management Among Young Muslims in Indonesia

Abstract: This research explored the religious practices as stress management among young Indonesian Muslims. The aim of the study was to explain how religiosity as experienced understood by a group of 12 young people studying at a large public Islamic university in Jakarta and could be managed them stress well. Interviews with the participants about their religious practices and stress management were analysed. Findings showed that religion played a role in the way the study participants managed stress. All of them had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This important finding confirms that of previous studies demonstrating that spirituality has an impact on the well-being of Indian university students (Deb and Strodl 2019), and that spirituality, religiousness, and personal beliefs may have impacts on medical school students' quality of life (Krägeloh et al 2015). While further investigation is needed to uncover how spiritual exercise can help students' mental health, the findings of this study support the claim that religious awareness can help mental stability (see Abdul-Rahman 2017; Joshanloo and Weijers 2019;Adriani 2018). This claim was confirmed during the discussion with the students when they found that letting things go and letting their destiny work on its own as effective solutions to facing the uncomforting situations that they experience in both their academic and non-academic lives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This important finding confirms that of previous studies demonstrating that spirituality has an impact on the well-being of Indian university students (Deb and Strodl 2019), and that spirituality, religiousness, and personal beliefs may have impacts on medical school students' quality of life (Krägeloh et al 2015). While further investigation is needed to uncover how spiritual exercise can help students' mental health, the findings of this study support the claim that religious awareness can help mental stability (see Abdul-Rahman 2017; Joshanloo and Weijers 2019;Adriani 2018). This claim was confirmed during the discussion with the students when they found that letting things go and letting their destiny work on its own as effective solutions to facing the uncomforting situations that they experience in both their academic and non-academic lives.…”
Section: Discussionsupporting
confidence: 89%
“…The discourse of well-being in education has been discussed in various academic forums in Indonesia. Indonesian scholars such as Wibowo et al (2021) and Adriani (2018) have argued for the inclusion of well-being in the Indonesian education context. While the general approach of Indonesian Islamic education towards student well-being remains closer to the Western approach to well-being, relying heavily on the hedonic and eudemonic perspectives, scholars such as Rizvi et al (2021) and Joshanloo and Weijers (2019) offer a dual approach to well-being in the sense that the Islamic approach to well-being that should enrich the Western approach by bringing another layer without dismissing the other two layers, that is, by acknowledging hedonic and eudemonic forms of well-being but treating them as pathways leading to the ultimate one, spiritual and transcendental well-being (See also Adriani 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prayer with full belief will give strength to individual. Adriani and Yustari (2019) To do study with method qualitative about religious practices as stress management among young Muslims in Indonesia. Findings on research this is that participant believe that religion can help in complete the problem that made it stress, among others with read the Koran and entered organization religious.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that affect happiness externally used in this study are social support obtained from individual social relationships. Jaafar in (Adriani Y., 2018) explains that several sources of Indonesian happiness include family, social relations, and self-fulfillment. Happiness can arise when individuals spend time with friends, exchange ideas, chat, and have fun (Lana and Indrawati, 2021).…”
Section: Introductionmentioning
confidence: 99%